SECONDARY METABOLITES FROM STEM BARK OF CALOPHYLLUM SCLEROPHYLLUM AND C. CASTANEUM (CLUSIACEAE) AS TYROSINE KINASE INHIBITORS AND ITS CYTOTOXIC ACTIVITIES - Widyo Wartono, Muhammad
Clusiaceae is a family of higher flowering plants consisting of 27 genera and 1090 species. Calophyllum is one of the main genera, with 190 species, 85 of which (45%) grow in Indonesia. This genus is distributed mainly in Southeast Asia, with diversity centers in Kalimantan, Sumatera, Papua, and the Malay Peninsula. The commercial products of these plants are mainly wood for timber and oil seeds for biodiesel. Until now, about 62 species of Calophyllum have been studied for their secondary metabolites, and six of them were from Indonesia. Phytochemical studies of Calophyllum showed that this genus is rich in xanthones, coumarins, chromanones, chromano-coumarins, flavonoids, phloroglucinols, terpenoids, steroids, benzoic acid derivatives, biphenyls, and phenyl glycosides. Chromanones, coumarins, and chromano-coumarins are characteristic of this genus. The distribution of each compound in the plant tissues of Calophyllum is different. Xanthones are abundant in stem bark and wood. Chromanones and coumarins are mainly found in stem bark and leaves. Flavonoids are found in the stem bark and leaves, while terpenoids are distributed in all plant tissues. Chromanones isolated from Calophyllum have certain characteristics, i.e., having a vicinal methyl group at C-2 and C-3. In addition, the aromatic skeleton is substituted by a carboxylic acid chain at C-6 or C-8 and isoprenyl at C-8 or C-6. The coumarin compound from Calophyllum has a characteristic, i.e., the presence of an alkyl or phenyl group at C-4, so it is often referred to as 4-alkyl/phenyl coumarins. Coumarins from Calophyllum can have an acyl group at C-6 or C-8, and some of them bind isoprenyl at C-6 or C-8. Chromano-coumarin compounds of this genus are compounds with a 2,3-dimethylchromanone skeleton that also have a coumarin ring at C-6 or C-8. Secondary metabolites of Calophyllum also have various bioactivities, including anticancer, antibacterial, antifungal, antiviral, and antioxidant properties. The compounds from Calophyllum, in particular, have high activity as anticancer and antiviral agents. Coumarins, chromano-coumarins, and xanthones were reported to have anticancer activity against several cell lines, such as PC3, K562, U251, KB, Hela S-3, HT-29, HepG2, SNU-1, HeLa, NCI-H23, Raji, LS174T, SK-MEL-28, and IMR-32. Meanwhile, the chromano-coumarin compounds have very significant activity to inhibit the growth of the HIV virus. Based on this background, the aim of this study was to obtain phytochemical and biological activity data for the Indonesian Calophyllum. To achieve the first objective, a phytochemical study was carried out on the stem bark of C. sclerophyllum and C. castaneum. Next, to achieve the second objective, the in vitro study of the anticancer activity of isolated compounds was carried out, namely cytotoxicity tests against murine leukemia P-388 cells and inhibition toward eight tyrosine kinase receptors (RTK), i.e. EGFR, HER2, HER4, IGF1R, InsR, KDR, PDGFR?, and PDGFR?, as well as studying the interaction of the isolated compounds that have significant activity against RTK by the in silico method. The research material used was the stem bark of C. sclerophyllum and C. castaneum collected from West Kalimantan. The isolation of compounds was carried out in several steps. The dried powder stembark extraction was conducted using the maceration method with acetone The fractionation of the acetone extract was carried out by vacuum liquid chromatography (VLC). The pure compounds obtained from the purification of VLC fractions using various chromatographic techniques, such as, radial chromatography (RC), column chromatography (CC), and medium-pressure liquid chromatography (MPLC). The structures of isolated compounds were determined based on spectroscopic data, including 1D NMR (1H and 13C NMR, and TOCSY-1D) and 2D NMR (HSQC, COSY, and HMBC), high resolution mass spectrometry (HRMS), physical data such as optical rotation, and data comparison with literature data. In vitro analysis of the cytotoxic activity of the isolated compounds against murine leukemia P-388 cells was performed following the MTT assay method, while tyrosine kinase inhibitors were tested by the bioluminescent assay method. Meanwhile, in silico analysis of the interactions of isolated compounds with inhibitory values for RTK was carried out for the EGFR, HER2, and PDGFR? using the molecular docking method using Autodock Vina®. In this study, 13 compounds have been successfully isolated and elucidated from the stem bark of C. sclerophyllum and C. castaneum. Six chromanones were obtained from C. sclerophyllum, namely (–)-trans-calolongic acid (5), (–)-cis-calolongic acid (6), (–)-trans-calolongic acid methyl ester (343), (–)-cis-calolongic acid methyl ester (344), (–)-trans-recedensic acid methyl ester (345), and (–)-trans-caloteymannic acid (346). Meanwhile, seven compounds were obtained from C. castaneum, including four chromanones, one xanthone, one chromano-coumarin, and one triterpenoid. The four chromanones are (+)-calofolic acid B (27), (+)-calofolic acid D (30), trans-apetalic acid (33) and (+)-calofolic acid D methyl ester (34). A chromano-coumarin, namely isorecedensolide (95), a xanthone, identified as caloxanthone C (237), and one triterpenoid, namely friedelin (326). Three chromanones, 343, 345, and 346, are new compounds, while compound 344 has been reported for the first time from plants, but it has been synthesized from 6. Of the ten chromanones, nine are pyranochromanones, and one compound (345) is a basic chromanone The finding of chromanone and chromano-coumarin suggests that there is a biogenesis relationship between the two compounds. It is supposed that chromanones are the intermediates in chromano-coumarin biogenesis. Compound 346 is suggested to be an intermediate in the biogenesis of soulatrolone (103) and (–)-soulatrolide (120). Meanwhile, compound 5 was suggested as an intermediate in the biogenesis of (–)-calanolide B (112), while compound 6 was suggested as an intermediate in the biogenetic of (–)-calanolide F (116). In the bioactivity study, eight isolated compounds were examined for their cytotoxic activity against murine leukemia P-388 cells using the MTT assay method. Three compounds, i.e., 6, 95, and 237, had moderate activity with IC50 of 26.9 µM, 20.7 µM, and 21.4 µM, respectively. Meanwhile, the other chromanones (5, 27, 30, 33, and 34) had less activity with an IC50 between 31?73 µM. Bioactivity studies showed that chromanones had lower activity than xanthones and chromano-coumarins. This activity is supposed to relate to the carboxylic group. Compound 30 (IC50 52.0 µM) is less active than the methyl ester (compound 34, IC50 32.1 µM). Compound 30 is also related to the biogenetic of 95, the difference is that the carboxylic acid chain forms a lactone ring while an isoprenyl remains free. Compound 95 had an IC50 of 20.7 µM which is more active than compound 30. Cis or trans positions of 2,3-dimethyl chromanone also affect bioactivity, cis-chromanone is more active than trans-chromanone, i.e., (–)-cis-calolongic acid (6; IC50 26.9 µM) has higher bioactivity than (–)-trans-calolongic acid (5; IC50 31.3 µM. While (+)-calofolic acid D (30; IC50 52.0 µM) is more active than (+)-trans-apetalic acid (33; IC50 73.2 µM). Tyrosine kinase inhibition of compounds 5, 30, 345 and 346, was tested at a concentration of 10 µM against eight RTKs (EGFR, HER2, HER4, IGF1R, InsR, KDR, PDGFR?? and PDGFR??? The test results for tyrosine kinase inhibitors showed that (–)-trans-recedensic acid methyl ester (345), gave the highest inhibition on EGFR and HER2, i.e,. 33% and 39%, respectively. Compound 345 showed a weak inhibition toward PDGFR?. Compound 345 was also the only one among chromanones to inhibit HER2, with a value of 39%. This value was slightly different when compared to the percent inhibition of erlotinib (338) of 47%. Trans-caloteysmanic acid (346) which gave the highest percent inhibition values of PDGFR? and PDGFR?, was 38% and 25%, respectively, while against EGFR only gave an inhibition value of 6%. Compound 346 has a pyranochromanone skeleton, and the presence of an additional phenyl group makes the molecules larger than the other compounds. The shape of this molecule is supposed to be more suitable compatible with the active sites of PDGFR? and PDGFR?. In the EGFR and HER2 enzymes, which are still in the same family, the active site of the enzyme is supposed to be more suitable for molecules that have a quinazoline-like skeleton, such as compound 345. (+)-Calofolic acid D gave the highest percent inhibition value to EGFR at 33% and to PDGFR? at 12%. (–)-Trans-calolongic acid (5) gave the highest percentage inhibition of EGFR, PDGFR? and PDGFR? of 29%, 23%, and 14%, respectively. The results of the inhibition test on EGFR and PDGFR? showed that all tested chromanones showed inhibition. Only compound 345 The finding of chromanone and chromano-coumarin suggests that there is a biogenesis relationship between the two compounds. It is supposed that chromanones are the intermediates in chromano-coumarin biogenesis. Compound 346 is suggested to be an intermediate in the biogenesis of soulatrolone (103) and (–)-soulatrolide (120). Meanwhile, compound 5 was suggested as an intermediate in the biogenesis of (–)-calanolide B (112), while compound 6 was suggested as an intermediate in the biogenetic of (–)-calanolide F (116). In the bioactivity study, eight isolated compounds were examined for their cytotoxic activity against murine leukemia P-388 cells using the MTT assay method. Three compounds, i.e., 6, 95, and 237, had moderate activity with IC50 of 26.9 µM, 20.7 µM, and 21.4 µM, respectively. Meanwhile, the other chromanones (5, 27, 30, 33, and 34) had less activity with an IC50 between 31?73 µM. Bioactivity studies showed that chromanones had lower activity than xanthones and chromano-coumarins. This activity is supposed to relate to the carboxylic group. Compound 30 (IC50 52.0 µM) is less active than the methyl ester (compound 34, IC50 32.1 µM). Compound 30 is also related to the biogenetic of 95, the difference is that the carboxylic acid chain forms a lactone ring while an isoprenyl remains free. Compound 95 had an IC50 of 20.7 µM which is more active than compound 30. Cis or trans positions of 2,3-dimethyl chromanone also affect bioactivity, cis-chromanone is more active than trans-chromanone, i.e., (–)-cis-calolongic acid (6; IC50 26.9 µM) has higher bioactivity than (–)-trans-calolongic acid (5; IC50 31.3 µM. While (+)-calofolic acid D (30; IC50 52.0 µM) is more active than (+)-trans-apetalic acid (33; IC50 73.2 µM). Tyrosine kinase inhibition of compounds 5, 30, 345 and 346, was tested at a concentration of 10 µM against eight RTKs (EGFR, HER2, HER4, IGF1R, InsR, KDR, PDGFR?? and PDGFR??? The test results for tyrosine kinase inhibitors showed that (–)-trans-recedensic acid methyl ester (345), gave the highest inhibition on EGFR and HER2, i.e,. 33% and 39%, respectively. Compound 345 showed a weak inhibition toward PDGFR?. Compound 345 was also the only one among chromanones to inhibit HER2, with a value of 39%. This value was slightly different when compared to the percent inhibition of erlotinib (338) of 47%. Trans-caloteysmanic acid (346) which gave the highest percent inhibition values of PDGFR? and PDGFR?, was 38% and 25%, respectively, while against EGFR only gave an inhibition value of 6%. Compound 346 has a pyranochromanone skeleton, and the presence of an additional phenyl group makes the molecules larger than the other compounds. The shape of this molecule is supposed to be more suitable compatible with the active sites of PDGFR? and PDGFR?. In the EGFR and HER2 enzymes, which are still in the same family, the active site of the enzyme is supposed to be more suitable for molecules that have a quinazoline-like skeleton, such as compound 345. (+)-Calofolic acid D gave the highest percent inhibition value to EGFR at 33% and to PDGFR? at 12%. (–)-Trans-calolongic acid (5) gave the highest percentage inhibition of EGFR, PDGFR? and PDGFR? of 29%, 23%, and 14%, respectively. The results of the inhibition test on EGFR and PDGFR? showed that all tested chromanones showed inhibition. Only compound 345